Cisco CCNP Security SNCF (Exam 300-710) - Sequeira, Anthony; Wong, Ronnie (Packt Publishing, 2024)
This course provides a comprehensive exploration of Cisco Firewall and IPS systems, optimized for deployment within the AWS ecosystem. It commences with a foundational overview, catering to both novices and seasoned professionals. Beginning with AWS Virtual Private Cloud (VPC) configuration, you'll establish the foundation for building secure network infrastructures. The course then focuses on deploying the Firepower Management Center virtual (FMCv), a pivotal component for effective security policy management and monitoring. You'll master the Next-Generation Firewall virtual (NGFWv) deployment within AWS, bolstering your ability to safeguard networks against evolving cyber threats. Hands-on labs and practical exercises are integrated to impart real-world skills in configuring, troubleshooting, and securing Cisco Firewall and IPS systems. You'll gain expertise in risk management, report generation, and effective troubleshooting techniques. By course completion, you'll be well-prepared for Cisco CCNP Security SNCF (Exam 300-710), poised to excel in the realm of cybersecurity. What you will learn Configure AWS VPC for Cisco Firewall and IPS systems Deploy and manage FMCv and NGFWv in AWS Implement NGFW Routed and Transparent modes Explore multi-instance deployments and clustering Troubleshoot using CLI/GUI and perform packet capture Enhance security with Cisco AMP and other integrations Audience This course is ideal for cybersecurity professionals and network administrators looking to advance their skills in Cisco Firewall and IPS systems. A basic understanding of networking concepts and AWS is preferred. About the Authors ACI Learning: ACI Learning trains leaders in Cybersecurity, Audit, and Information Technology. Whether starting an IT career, mastering a profession, or developing a team, they provide essential support at every step. Anthony Sequeira: Anthony Sequeira, CCIE #15626, is a seasoned tech trainer and author with expertise in cloud, cybersecurity, and IT. His IT journey began in 1994 at IBM in Tampa, Florida. He later founded Computer Solutions but discovered his true passion for teaching and writing about technology. In 1996, he joined Mastering Computers, which evolved into KnowledgeNet, where he continued to share the latest tech advancements. Today, he serves as a full-time Edutainer at ACI Learning, delivering global training and authoring textbooks on modern technologies. He holds certifications like CCIE R&S #15626, as well as numerous others from AWS, CompTIA, Juniper, and Microsoft, among others. Anthony's expertise spans the IT landscape. Ronnie Wong: Ronnie Wong has had a diverse career, from diesel service and ministry to computer repair and network administration in small businesses. He set up networks and servers and created policies in these roles. As an Edutainer at ITProTV, now ACI Learning, he started as an IT technical instructor, later working as a contract trainer for the University of Florida, Marion County School Systems, and Nationwide Insurance. He provided Cisco, Microsoft Windows, CompTIA, and IT security training to military and DoD personnel. Now the Director of Content Development at ACI Learning, Ronnie's credentials include CCNP Enterprise Infrastructure, CCNA, CompTIA's A+, Network+, Security+, ISC2 CC, CNA Security, and PCNSA.
Online resource; title from title details screen (O'Reilly, viewed January 30, 2024)
Keywords: Cisco Systems, Inc -- Study guides -- Examinations; Electronic data processing personnel -- Study guides -- Certification; Computer networks -- Study guides -- Examinations; Réseaux d'ordinateurs; Examens; Guides de l'étudiant; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet